2008
DOI: 10.1002/ceat.200700449
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Hydrocyclone Classification Efficiency for Fine Particles by Introducing a Volute Chamber with a Pre‐Sedimentation Function

Abstract: A new hydrocyclone was designed with a volute chamber positioned prior to the inlet. Since the volute chamber prior to the inlet has a pre-sedimentation function due to the centrifugal sedimentation effect, coarse particles are concentrated on the outer side and fine particles are concentrated on the inner side as the particles reach the entrance of the hydrocyclone. Consequently, coarse particles in the hydrocyclone are easily separated into the underflow and fine particles are easily transferred into the ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Due to the cost of experimental programs in terms of time and materials, and with the development of computational fluid dynamics (CFD) simulation, many researchers have chosen to use CFD to conduct parametric studies to arrive at a shortlist of possible designs for further experimental investigations and to study the flow field in a hydrocyclone. These CFD simulations have produced results that are in good agreement with those obtained by experiment [12]. For those hydrocyclones that are used for particle separation and water-oil separation, researchers place greater emphasis on the liquid-solid and liquid-liquid hydrocyclone simulations [7,17,23].…”
Section: Introductionsupporting
confidence: 67%
“…Due to the cost of experimental programs in terms of time and materials, and with the development of computational fluid dynamics (CFD) simulation, many researchers have chosen to use CFD to conduct parametric studies to arrive at a shortlist of possible designs for further experimental investigations and to study the flow field in a hydrocyclone. These CFD simulations have produced results that are in good agreement with those obtained by experiment [12]. For those hydrocyclones that are used for particle separation and water-oil separation, researchers place greater emphasis on the liquid-solid and liquid-liquid hydrocyclone simulations [7,17,23].…”
Section: Introductionsupporting
confidence: 67%
“…Once pressurized into a hydrocyclone, powders are separated by separation: coarse/dense particles shift to the sidewall due to relatively large centrifugal forces, join the underflow via an outer swirl and leave via an underflow outlet; fine/sparse particles shift to the core due to relatively small centrifugal forces, join the overflow via an inner swirl and leave via an overflow pipe. One-stage grading by conventional hydrocyclones leads to coarse particle underflow and fine particle overflow only [8][9][10][11][12][13]. As shown in Figure 1, the size range is over-wide and fine grading has not been achieved, resulting in poor grading efficiency and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out with traditional hydrocyclone families have shown that, depending on the geometry, changing the impermeable conical wall to a porous one provides good results in terms of energy cost reduction [15,16] or efficiency increase [17]. Besides, some studies proposed modifying the inlet configuration [18][19][20], the vortex finder size and shape [21][22][23], the conical section [24][25][26], the overflow diameter [27], and other geometric dimensions of hydrocyclones [28,29]. Optimization techniques, such as differential evolution algorithms [30] and response surfaces [31], presented optimized geometric proportions to improve the performance of conventional [32,33] and filtering hydrocyclones [34].…”
Section: Introductionmentioning
confidence: 99%